Staging Chinese Kiwi voices : Chinese representations in New Zealand theatre : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - Lam, Cynthia Hiu Ying (Massey University, 2019)
This thesis explores how Chinese Kiwi theatre makers challenge hegemonic discourses regarding representations of Chinese people in theatre. Up until 1996, narratives and representations of Chinese people in mainstream New Zealand media have been muted, objectified, or confined to fixed stereotypes. In this study, I demonstrate how four contemporary Chinese Kiwi theatre artists have (re)negotiated, reclaimed, and rewritten the subjectivity and narratives of Chinese people in New Zealand. This will be examined within the postcolonial and binational framework that is specific to Aotearoa. Through the examination of specific theatrical works by Lynda Chanwai-Earle, Renee Liang, Mei-Lin Te Puea Hansen, and Alice Canton, I demonstrate how they have challenged hegemonic discourses and Pākehā-narrated histories regarding the Chinese. Their works cover the lives of the early Chinese mining community (referred to as the ‘old Chinese’), to more contemporary representations (the ‘new Chinese’) that involve different sub-sets within the community. The relationship and tensions between Māori, Chinese and Pākehā will be analysed throughout. The subjectivity of Chinese women will also be reclaimed by debunking the stereotype of the ‘Oriental woman’ through matrilineal narratives and autobiography. Finally, the transformative and reconciliatory impact of their works will be examined and dissected. In this thesis, I argue that the work of the Chinese Kiwi artists I explore gestures to the need to negotiate the Chinese place, or ‘non-place’, within the dominant hegemonic narrative. I argue that these artists make strong claims through their work for the bicultural framework that privileges the Māori-Pākehā dialogue to be expanded to include the Chinese voice. I conclude that the Chinese Kiwi theatre artists have propelled the once muted Chinese voice from the margins, and have begun to carve a space into the dominant New Zealand narrative.
Keywords: Chinese New Zealanders; Women immigrants; New Zealand; Drama; Chinese; Gold mines and mining; Otago; History; Race relations; New Zealand drama; History and criticism; Chanwai-Earle, Lynda; Liang, Renee; Te Puea Hansen, Mei-Lin; Canton, Alice; Criticism and interpretation